Tom Blackwell : the complete paintings, 1970-2014 - Chase, Linda, 1942- (The Artist Book Foundation, 2015)
Tom Blackwell (born 1938) is primarily known for his work in photorealism, a movement characterized by its ardent embrace of photographic source material. In 1969, he began a series of brashly beautiful motorcycle paintings that established him as one of the founders and foremost artists of the movement. In his equally celebrated store-window paintings, Blackwell captures the counterpoint between the idealized reality within the store display and the bustling urban life reflected in the glass. As author Linda Chase remarks in her essay, The magic of these paintings resides in the artist's ability to transform the arbitrary photographic information into dynamic and complex artistic compositions, revealing and clarifying the image while preserving its mystery. The first comprehensive resource on an icon of photorealism, this volume includes further essays by esteemed art writers Louis K. Meisel and Carter Ratcliff.